Nursing in pain management at urgency and emergency care units - Paulo Eduardo Pires de Oliveira; Lilian Varanda Pereira; Nilde Resplandes Santos; Layz Alves Ferreira Souza (Universidade Federal de Goias, 2016)
Nursing must manage pain in urgency and emergency care based on scientific evidences but there seems to be obstacles to this practice. The objective of this study was to identify and analyze pain management strategies and barriers for their use among the nursing professional categories at urgency and emergency care units. An integrative review was conducted with searches on LILACS, SciVerse Scopus, PUBMED, and in the Academic Google grey literature. Fifteen articles published between 2012 and 2015 were selected. Nursing professionals assessed pain characteristics through anamneses and use of instruments. Interventions were primarily limited to pharmacological ones, pointing to the need to associate them with non-pharmacological interventions. The monitoring of pain is still incipient. Professionals need to further the use of valid instruments for pain assessment, intervention, and monitoring to overcome the barriers faced by professionals, patients, and managers at urgency and emergency units to systematize its management.